A Critical Analysis of Intimate Partner Sexual Violence in Iran - Naghavi, Azam; Amani, Shoale; Bagheri, Marzieh; De Mol, Jan (Frontiers in Psychology, 2019)
According to global data, intimate partner violence and its corresponding impact threaten the lives of almost 35 percent of women at some point in their life. The aim of this research was to explore the effects of intimate partner sexual violence on women’s sense of self-efficacy when it comes to speaking out against violence and seeking help. In-depth interviews and a thematic analysis approach were employed to collect and analyze the data. The participants were 10 women with experiences of intimate partner sexual violence. They were selected through purposive and snowball sampling. Two main themes were drawn from the data, including Exposure and Empowerment. Exposure refers to the type of violence women have experienced and its physical and emotional effects; and Empowerment refers to factors women considered as giving them the courage to speak out against perpetrators, to seek help from others, or to refrain from doing either. It is concluded that Iranian women are not passive when exposed to intimate partner sexual violence, and social support, mainly from family and friends, was a pathway to feelings of empowerment; without this support, women’s emotional health is put in jeopardy. Due to the importance of social networks in creating a sense of empowerment, it is recommended that professionals involved in cases of intimate partner sexual violence create an alliance with the women’s families and friend and educate them on how to prevent violence or offer help before the violence takes its toll on woman’s emotional and physical wellbeing.